2017
DOI: 10.1016/j.vaccine.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinician knowledge, clinician barriers, and perceived parental barriers regarding human papillomavirus vaccination: Association with initiation and completion rates

Abstract: Purpose We tested the hypothesis that clinician knowledge, clinician barriers, and perceived parental barriers relevant to the human papillomavirus (HPV) vaccination account for the variation in vaccine delivery at the practice-site level. Methods We conducted a survey from October 2015 through January 2016 among primary care clinicians (n=280) in a 27-county geographic region to assess clinician knowledge, clinician barriers, and perceived parental barriers regarding HPV vaccination. Primary care clinicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 20 publications
5
51
0
1
Order By: Relevance
“…The methods and results associated with the larger investigation are reported elsewhere (Rutten et al. ). We compared two mixed‐mode designs (sequential: mail/web and sequential: web/mail) to two single‐mode designs (mail‐only and web‐only), with respect to response rate and nonresponse bias.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods and results associated with the larger investigation are reported elsewhere (Rutten et al. ). We compared two mixed‐mode designs (sequential: mail/web and sequential: web/mail) to two single‐mode designs (mail‐only and web‐only), with respect to response rate and nonresponse bias.…”
Section: Methodsmentioning
confidence: 99%
“…This study was embedded in a larger survey study conducted from October 2015 to January 2016 and designed to assess clinician knowledge, clinician barriers, and perceived parental barriers regarding HPV vaccination using a validated instrument. The methods and results associated with the larger investigation are reported elsewhere (Rutten et al 2017). We compared two mixed-mode designs (sequential: mail/web and sequential: web/mail) to two single-mode designs (mail-only and web-only), with respect to response rate and nonresponse bias.…”
Section: Study Design and Survey Instrumentmentioning
confidence: 99%
“…We conducted a survey of primary care clinicians in a 27-county geographic region captured by the Rochester Epidemiology Project (REP) using a validated instrument to assess clinician knowledge, attitudes, and behaviors related to HPV vaccination[2023]. The REP is a research infrastructure that links medical records from the majority of clinical practices across the 27 counties to individuals residing in the community and maintains an electronic index of medical record information, including clinical diagnoses, procedure codes, drug prescriptions, office visits, emergency room visits, and hospitalizations.…”
Section: Methodsmentioning
confidence: 99%
“…[20, 21, 23] The survey included questions to assess clinicians’ knowledge, attitudes, and behaviors related to HPV and HPV vaccination. Clinicians were asked to rate the frequency with which they recommended the HPV vaccine separately for their female and male patients: In the past 12 months, how often did you recommend the HPV vaccine to your female [male] patients?…”
Section: Methodsmentioning
confidence: 99%
“…In consonance with these results, a study conducted in 2007 concluded that despite the difficulties faced, health centres operating within schools are important disseminators of preventive care for vulnerable adolescents and youths (Rutten et al. ). Therefore, one way to revise these representations, as shown in the studies above, is to ensure a more effective presence of health services in schools.…”
Section: Discussionmentioning
confidence: 93%